Hybrid composites of lanthanide metal–organic frameworks with epoxy silanes for highly sensitive thermometry. Issue 41 (5th October 2022) - Shu, Ying; Guan, Huiru; Kirillov, Alexander M.; Liu, Weisheng; Yang, Lizi; Dou, Wei
Abstract : A new series of lanthanide MOF-based composites with epoxy silanes were fabricated by means of a curing reaction between Ln-BTB and ECTMS or KH563 and their fluorescence properties and efficacy in the temperature sensing of materials were improved. Abstract : Post-synthetic modification of metal–organic frameworks (MOFs) and fabrication of hybrid composites are currently hot topics in the development of new functional materials. In this study, a facile and direct approach for coupling of lanthanide MOFs with epoxy silanes was developed, providing an access to a new series of functional composites. Two types of commercially available epoxy silane, namely 2-(3, 4-epoxycyclohexyl)ethyltrimethoxysilane (ECTMS) and (3-glycidoxypropyl)methyl diethoxysilane (KH563), were used to modify Ln-BTB MOFs ([Ln(BTB)(H2 O)] n ·2 n (C6 H12 O); Ln = Tb or Eu0.001 Tb0.999 ; H3 BTB = 1, 3, 5-benzenetrisbenzoic acid) via covalent grafting involving mechanical grinding, epoxide coupling and curing reactions. The fabricated composites (Tb-BTB@ECTMS, Eu0.001 Tb0.999 -BTB@ECTMS, Tb-BTB@KH563, Eu0.001 Tb0.999 -BTB@KH563) and their Ln-MOF precursors were fully characterized, including a detailed study of their stability and fluorescence properties. The obtained composites show high thermal and solution stability, under boiling water conditions and in a wide pH range of 1–12. Application of the composites as temperature sensors in the 197–297 K and 273–343 K temperature ranges was explored in detail, revealing a remarkable sensing behavior. For example, Tb-BTB@ECTMS shows a maximum relative sensitivity ( S r ) of 6.85% K −1 at 343 K. Eu0.001 Tb0.999 -BTB@ECTMS represents a white-light emission material with the CIE coordinates (0.3194, 0.3049) that are very close to those of white light, along with good temperature sensing performance and a relative sensitivity of 4.32% K −1 at 297 K. An enhanced performance of the composites in comparison with the parent MOF materials as well as the mechanism of energy transfer were rationalized by DFT calculations. By unveiling a facile and efficient method for improving the stability of luminescent MOFs, via post-synthetic grafting with epoxy silanes, the present study will stimulate further research at the interface of materials chemistry, MOF design, photoluminescence and temperature sensing.